Razprava o pomenu izstavitve zemljiškoknjižnega dovolila in o nekaterih posledicah spremenjene ureditve izbrisne tožbe - Hudej, Jasna (Pravni letopis, 2013)
The authors firstly discuss the meaning of an issued land register permission and deal with the question, whether the position of the acquirer of the ownership right obtained by way of legal transaction is secured prior to entry in the land register. Furthermore, they analyse how the changed regulation regarding a claim for removal from the land register affects the position of an obligational right holder in the enforcement procedure initiated by the alienator's creditor. The authors also present the solution of multiple disposal situations in terms of the new perspectives on the meaning of an issued land register permission.
Keywords: lastninska pravica; nepremičnine; prenos; vpis; zemljiške knjige